Interleukin-6-induced neuroinflammation is exacerbated by subclinical levels of interferon-α - Songkhunawej, Pattama; Hofer, Markus J. (Frontiers in Neuroscience, 2025)
IntroductionCerebral cytokinopathies are key examples of dysregulated cytokine responses. While mouse models with targeted production of individual cytokines have been pivotal in establishing a causal link between cytokines and disease— especially in the central nervous system—they often fail to replicate the complex inflammatory environments seen in various neuropathological conditions, such as neuromyelitis optica spectrum disorder, where multiple cytokines are upregulated.MethodsTo address this, we developed a novel mouse model, GFAP-IL6-IFNlo mice, by combining transgenic mice with astrocyte-targeted production of IL-6 (GFAP-IL6 mice) and IFN-α (GFAP-IFNlo mice).ResultsOur findings reveal that chronic, low-level production of IFN-α, below the typical disease-inducing threshold, significantly accelerates disease progression in GFAP-IL6-IFNlo mice compared to GFAP-IL6 mice. The double transgenic mice exhibited progressive ataxia, persistent seizure-like episodes, and reduced survival. Remarkably, the clinical and pathological symptoms remained predominantly IL-6-driven and required the presence of adaptive immune cells.ConclusionIn summary, we demonstrate that subclinical levels of IFN-α can markedly exacerbate IL-6-mediated neurological disease, suggesting that future studies, should consider the combined effects of IL-6 and IFN-α.